Hypericin-Mediated Photodynamic Therapy for Head and Neck Cancers: A Systematic Review - Jakub Fiegler-Rudol; Natalia Zięba; Radosław Turski; Maciej Misiołek; Rafał Wiench (Biomedicines)
Background: Conventional treatments for cancers of the head and neck region are often associated with high recurrence rates and impaired quality of life. Photodynamic therapy (PDT) has emerged as a promising alternative, leveraging photosensitizers such as hypericin to selectively target tumour cells with minimal damage to surrounding healthy tissues. Objectives: We aimed to evaluate the efficacy and underlying mechanisms of hypericin-mediated PDT (HY-PDT) in treating head and neck cancers. Methods: Adhering to PRISMA 2020 guidelines, a systematic search was conducted across PubMed/Medline, Embase, Scopus, and the Cochrane Library for studies published between January 2000 and December 2024. Inclusion criteria encompassed preclinical in vitro and in vivo studies and clinical trials focusing on HY-PDT for head and neck malignancies and its subtypes. Results: A total of 13 studies met the inclusion criteria, comprising both in vitro and in vivo investigations. HY-PDT consistently demonstrated significant cytotoxicity against squamous cell carcinoma cells through apoptotic and necrotic pathways, primarily mediated by ROS generation. Hypericin exhibited selective uptake in cancer cells over normal keratinocytes. Additionally, HY-PDT modulated the tumour microenvironment by altering cytokine profiles, such as by increasing IL-20 and sIL-6R levels, which may enhance antitumor immunity and reduce metastasis. Conclusions: HY-PDT emerges as a highly promising and minimally toxic treatment modality for head and neck cancers, demonstrating efficacy in inducing selective tumour cell death and modulating the immune microenvironment. Despite the encouraging preclinical evidence, significant methodological variability and limited clinical data necessitate further large-scale, standardized and randomized controlled trials.